Research progresses on VOCs emission investigations via surface and satellite observations in China. Issue 11 (24th August 2022) - Li, Xinhe; Li, Bowei; Guo, Liya; Feng, Rui; Fang, Xuekun
Abstract : 1. Investigation of the VOCs emissions and source structure is summarized. 2. Characteristics of VOCs observations including surface and satellite are introduced. 3. Suggestions on improvement for future VOCs observation are provided. Abstract : Volatile organic compounds (VOCs) are important precursors of severe pollution of ozone (O3 ) and secondary organic aerosols in China. Fully understanding the VOCs emission is crucial for making regulations to improve air quality. This study reviews the published studies on atmospheric VOCs concentration observations in China and observation-based estimation of China's VOCs emission strengths and emission source structures. The results reveal that direct sampling and stainless-steel-tank sampling are the most commonly used methods for online and offline observations in China, respectively. The GC-MS/FID is the most commonly used VOCs measuring instrument in China (in 60.8% of the studies we summarized). Numerous studies conducted observation campaigns in urban areas (76.2%) than in suburban (17.1%), rural (18.1%), and background areas (14.3%) in China. Moreover, observation sites are largely set in eastern China (83.8%). Though there are published studies reporting observation-based China's VOCs emission investigation, these kinds of studies are still limited, and gaps are found between the results of top-down investigation and bottom-up inventories of VOCs emissions in China. In order to enhance the observation-based VOCs emission investigations in China, this study suggests future improvements including: (1) development of VOCs detection techniques, (2) strengthening of atmospheric VOCs observations, (3) improvement of the accuracy of observation-based VOCs emission estimations, and (4) facilitation of better VOCs emission inventories in China.